Association between N363S and BcLI Polymorphisms of the Glucocorticoid Receptor Gene (NR3C1) and Glucocorticoid Treatment-Related Side Effects in Acute Lymphoblastic Leukemia Patients: A Study from Khyber Pakhtunkhwa, Pakistan - Farid , Nayab; Farooq, Nazish; Bashir , Sobia; Naveed , Mian; Zahra , Maryam (Indus Journal of Bioscience Research, 2025)
Objectives: To evaluate the association between N363S and BcLI polymorphisms of the NR3C1 gene and glucocorticoid treatment-related side effects in acute lymphoblastic leukemia patients. Study design and setting: A Cross-sectional study was conducted at the Department of Hematology, Hayatabad Medical Complex, Peshawar from January 2023 to December 2023. Methods: A total of 88 patients aging between 6 months to 25 years newly diagnosed with acute lymphoblastic leukemia were included in this study. Patients received induction chemotherapy, which included a glucocorticoid treatment regimen consisting of dexamethasone, administered at a dose of 6 mg/m² daily, which was continued for a duration of 28 days within the induction phase consisting of 6 weeks. Metabolic and biochemical parameters were measured at baseline and after completing the 28-day dexamethasone treatment course. Primary outcomes included evaluating the clinical manifestations of glucocorticoid treatment related side effects and association between polymorphisms of the Glucocorticoid Receptor Gene (NR3C1) and these adverse effects. Results: The mean age of patients in this study was 12.56 ± 5.1 years with an age range of 6 months to 25 years. The sample consisted of 70.5% males and 29.5% females. Glucocorticoid treatment significantly increased hyperglycemia (p<0.001), hypertension (p=0.002), hypertriglyceridemia (p<0.001), dyslipidemia (p<0.001), elevated ALT (p=0.034), elevated ALP (p<0.001), and Cushingoid features (p<0.001). In N363S genotype analysis, hyperglycemia (p=0.03) and hypertension (p=0.02) showed significant associations, while BcLI genotype showed no significant associations with any parameter. Conclusion: Genetic screening for NR3C1 polymorphism can enable personalized glucocorticoid therapy in the patients of Acute Lymphoblastic Leukemia to minimize treatment-related metabolic complications.